PERTANGGUNGJAWABAN PENYITAAN OLEH SATUAN POLISI PAMONG PRAJA DALAM PELAKSANAAN RAZIA PENERTIBAN PEDAGANG KAKI LIMA DI KOTA SAMARINDA - Risky Sektiadi (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACTStreet vendors (STREET VENDORS) is one of the perpetrators of the economic populist who is engaged in the informal sector trade efforts. The term five-foot stems from Netherlands colonial occupation where sidewalk width 150 cm or